Emerging markets and cross-cultural distance: an revisiting of drivers of sme internationalization process - Scalamonti, Francesco (Piccola Impresa / Small Business, 2020)
Small and medium-sized enterprises (SMEs), often find certain difficulties in starting internationalization processes, especially if the target markets are distinguishable by a liability of foreignness, which makes them, the most difficult markets to have to approach, but which may also represent important opportunities for the future development of the business, as are the emerging ones. The present discussant paper aims to place itself within this line of studies to try to offer a direct theoretical framework to interpretation of internationalization strategies of SMEs in emerging markets, thus highlighting the drivers that can influence the variety of strategic behaviours. The implications that lie ahead are twofold. In the first place, bringing to attention of managers and entrepreneurs a series of possible strategic approaches that can be pursued in the current phase of globalization to penetrate emerging markets, characterized then by an intercultural distance. Secondly, it wants to be an updated theoretical tool supporting analysts and researchers, which they can also use for subsequent empirical analyzes.